The role of education in self-employment success - Aki Kangasharju; Sari Pekkala (University of Kent, Department of Economics, 2001)
This paper analyses the effect of the education of the self-employed on the success of their firms during economic downturn and upturn in the 1990s in Finland. We find that the business cycle affects the relative closure rates of firms run by the self-employed with any level of education. Exit probability is lower for the highly educated during bust, but higher in boom. This is accounted for by two facts. First, running a small firm is argued to be a less attractive choice to wage work particularly for the highly educated due to lower earnings prospects, less stable stream of earnings and the cultural tradition of working in large corporations. Second, the highly educated face a higher outside demand for their labour than the less educated during economic upturn. Finally, we find that regardless of the state of the aggregate economy, firms run by the highly educated have higher growth probabilities than those run by less educated ones.
Keywords: D21; E32; I29; 330; Education; self-employment; firm growth; exit; selectivity; Selbstständige; Unternehmensgründung; Schätzung; Finnland; Bildungsabschluss